Fake news and self-regulation. IN Commentary [column] - Maslog, Crispin C. (2017)
Professionalizing media practitioners combined with educating consumers is a way to prevent fake news from spreading.
Keywords: Fake news; Uson, Esther Margaux Justiniano; Nieto, Rey Joseph; Tordesillas, Ellen; Angeles, Maria Lourdes Nancy Binay